Pengaruh Siklus Operasi Terhadap Likuiditas Dan Modal Kerja (Studi Kasus PT Semen Gresik Tbk dan PT Holcim Indonesia Tbk) - Muktiadji, Nusa; Oktaria, Yesi (Jurnal Ilmiah Ranggagading (JIR), 2010)
Operating cycle is an important matter in a company. because by that operating cycle, it can be found out whether the company has been running well in day-to-day business. In addition, we can also find out whether the company is able to meet its financial obligations in due time. The goal of this research is to find out how high the influence of operating cycle against liquidity and working capital of the company. This study is conducted by using cases at PT. Semen Gresik Tbk and PT. Holcim Indonesia Tbk. Those companies are cement producers and distributors. The results of this research shows that in PT. Semen Gresik Tbk operating cycles as independent variable (X) has a very strong influence against liquidity as dependent variable (Y1) with level of significance 0.099 or 9.9%. While in PT. Holcim Indonesia Tbk the influence of variable-X against variable-Y statitically is not significant = 0.511 or 51.1%. It also shows that in PT. Semen Gresik Tbk between variable-X that is operating cycles and variable-Y that is net working capital (Y2) statistically has not significant influence = 0.364 or 36.4%. While in PT. Holcim Indonesia Tbk between variable-X and variabel-Y that is indicated by operating cycle (X) and net working capital (Y2) respectively shows not significant influence =0.842 or 84.2%. This condition is caused by the fact that. PT. Semen Gresik Tbk can manage well its financial performance. While PT. Holcim Indonesia Tbk has a lack of good management in managing trade account receivables and inventory. Keywords : cycle operations, liquidity, net working capital